THE EFFECT OF GIVING WATER EXTRACT OF FERMENTED PAPAYA LEAVES (Carica papaya L.) THROUGH DRINKING WATER ON THE PERFORMANCE OF SUPERIOR KAMPUNG CHICKEN BALIBANGTAN (KUB) - N. K. A., Susiani; Siti, N. W.; Witariadi, N. M. (Jurnal Peternakan Tropika; Vol 12 No 4 (2024): Vol. 12 No. 4 Tahun 2024; July - August, 2024)
This study aims to determine the effect of administering fermented papaya leaf water extract through drinking water on the performance of Superiorkampung chicken Balitbangtan (KUB). This research was carried out in Banjar Dinas Demung, Demung Village, Kediri District, Tabanan Regency, Bali, which lasted for 8 weeks. The design used was a completely randomized design (CRD) consisting of four treatments and four replications. Each replication contained three KUB chickens so the total number of KUB chickens used was 48 KUB chickens. The fermented papaya leaf water extract treatment given to KUB chickens was: 0% fermented papaya leaf water extract (P0), 2% fermented papaya leaf water extract (P1), 4% fermented papaya leaf water extract (P2) and 6% water extract fermented papaya leaves (P3). The variables observed were ration consumption, drinking water consumption, initial body weight, final body weight, body weight gain and feed conversion ratio. The results showed that administration of fermented papaya leaf water extract at levels of 2%, 4% and 6% via drinking water had no significant effect (P>0.05) on ration consumption, drinking water consumption, initial and final body weight, body weight gain. , and feed conversion ratio. From this research it can be concluded that administering fermented papaya leaf water extract at a level of 2-6% through drinking water does not affect the appearance of KUB chickens.